2017
DOI: 10.1016/j.molstruc.2016.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of structure in near-infrared fluorescent proteins by binding of biliverdin chromophore

Abstract: Near-infrared fluorescent proteins (NIR FPs) engineered from bacterial phytochromes and their mutants with different location of Cys residues, which able to bind a biliverdin chromophore, or without these Cys residues were studied using intrinsic tryptophan fluorescence, NIR fluorescence and circular dichroism. It was shown that a covalent binding of the biliverdin chromophore to a Cys residue via thioether group substantially stabilizes the spatial structure of NIR FPs. The stability of the protein structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…BphP1-FP showed the most stable structure as compared to BphP1-FP/C15S, as well as to other variants ( Figure 5 ). Dimeric NIR FPs with the Cys residues in both PAS and GAF domains were also characterized by the increased protein stability relative to their single-Cys variants [ 28 , 40 ]. We previously assumed that the Cys residue at position 15 affects the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…BphP1-FP showed the most stable structure as compared to BphP1-FP/C15S, as well as to other variants ( Figure 5 ). Dimeric NIR FPs with the Cys residues in both PAS and GAF domains were also characterized by the increased protein stability relative to their single-Cys variants [ 28 , 40 ]. We previously assumed that the Cys residue at position 15 affects the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…The tryptophan fluorescence spectra of the analyzed proteins assembled with PCB and iRFP713/BV normalized to unity at the maximum were superimposed well in the short-wave spectral region but differed in the long-wave spectral edge (Supplementary Figure S2). We have previously shown that an effective energy transfer from the tryptophan residue Trp281 of iRFP713 to BV takes place [37]. Based on this, the observed difference in the tryptophan fluorescence spectra of PCB-bound iRFP713 variants and BV-bound iRFP713 can be explained by the higher efficiency of nonradiative energy transfer from Trp281 to PCB than to BV.…”
Section: Resultsmentioning
confidence: 90%
“…The increased fluorescence quantum yield of the tryptophan residues W281 and W311 of iRFP713 at the intermediate state is explained by the absence of the conditions for the effective nonradiative energy transfer from tryptophan residues of the protein to the chromophore (Stepanenko et al, 2014; Stepanenko et al, 2017). The fact that the formation of the intermediate state was not accompanied by any increase in fluorescence intensity of iRFP713-W109 may be connected with less efficient nonradiative energy transfer from this residue to the chromophore compared to the other tryptophan residues, as W109 is the most distant tryptophan residue from the pocket of the GAF domain of iRFP713 (Stepanenko et al, 2017). An increase in the parameter A of iRFP713-W311 in the holoform, which was observed in the range of GdnHCl concentrations from 1.5 to 2.3–2.5 M, is obviously related with the re-shielding of this tryptophan residue in the intermediate state of iRFP713 (Fig.…”
Section: Resultsmentioning
confidence: 99%